2018
DOI: 10.1002/cm.21450
|View full text |Cite
|
Sign up to set email alerts
|

Septin 9 isoform 1 (SEPT9_i1) specifically interacts with importin‐α7 to drive hypoxia‐inducible factor (HIF)‐1α nuclear translocation

Abstract: We have shown previously that septin 9 isoform 1 (SEPT9_i1) protein associates with hypoxia-inducible factor (HIF)-1α to augment HIF-1 transcriptional activity by driving its importin-α-mediated nuclear translocation. Using in vitro and in vivo binding assays we identified that HIF-1α interacts with importin-α5 and importin-α7 in prostate cancer cells but only importin-α7 interacts with SEPT9_i1. The interaction with importin-α7 was dependent on the first 25 amino acids of SEPT9_i1 that are unique compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The notion that blebgenerated curvature could recruit septins to the plasma membrane upon cell detachment is supported by previous work 39,40 , though we found no reports of an explicit connection between bleb-related surface curvature and septin recruitment. Septins are known to scaffold and regulate factors from diverse signaling pathways [41][42][43][44] , including pro-survival pathways in cancer cells such as HIF-1 [45][46][47] , EGFR 48 , MET 49,50 , JNK 51 , and HER2 52 . Therefore, we hypothesized that bleb-dependent anoikis resistance could be achieved through recruitment of curvature-sensitive septin proteins to the plasma membrane via bleb-generated curvature, where they promote pro-survival signaling.…”
Section: Bleb-generated Plasma Membrane Curvature Drives the Formation Of Cortical Septin Structuresmentioning
confidence: 99%
“…The notion that blebgenerated curvature could recruit septins to the plasma membrane upon cell detachment is supported by previous work 39,40 , though we found no reports of an explicit connection between bleb-related surface curvature and septin recruitment. Septins are known to scaffold and regulate factors from diverse signaling pathways [41][42][43][44] , including pro-survival pathways in cancer cells such as HIF-1 [45][46][47] , EGFR 48 , MET 49,50 , JNK 51 , and HER2 52 . Therefore, we hypothesized that bleb-dependent anoikis resistance could be achieved through recruitment of curvature-sensitive septin proteins to the plasma membrane via bleb-generated curvature, where they promote pro-survival signaling.…”
Section: Bleb-generated Plasma Membrane Curvature Drives the Formation Of Cortical Septin Structuresmentioning
confidence: 99%
“…However, it is not yet known which isotypes of importin α drive the nuclear translocation of HIF1 α in stem cells. In addition, a recent study of prostate cancer cells showed that isoform 1 of Septin 9, a GTP-binding protein, facilitates HIF1 α nuclear translocation via its interaction with importin α 7 (112). Likewise, calcium stimulates interactions between S100A6 and armadillo repeats of importin α , followed by the inhibition of NLS formation of cargo–importin α transport complexes that regulate the nuclear translocation of cargo proteins (113).…”
Section: Hif1α Regulatory Factorsmentioning
confidence: 99%
“…Therefore, research on the target of Hif-1 α has currently become a topic of great interest. It has been shown that Sept9 can bind and stabilize Hif-1 α , promote its transcriptional expression, and promote angiogenesis and tumor growth [ 12 , 13 ]. By using Chinese Glioma Genome Atlas (CGGA) gene correlation analysis, it was discovered the significant positive correlation between Sept9 and Hif-1 α .…”
Section: Introductionmentioning
confidence: 99%